Mesomorphic phase transitions of 3F7HPhF studied by complementary methods. (1st February 2018) - Deptuch, Aleksandra; Jaworska-Gołąb, Teresa; Marzec, Monika; Pociecha, Damian; Fitas, Jakub; Żurowska, Magdalena; Tykarska, Marzena; Hooper, James
ABSTRACT: Physical properties and the phase sequence of (S)-4′-(1-methylheptyloxycarbonyl)biphenyl-4-yl 4-[7-(2, 2, 3, 3, 4, 4, 4-heptafluorobutoxy) heptyl-1-oxy]-2-fluorobenzoate exhibiting the liquid crystalline paraelectric smectic A*, ferroelectric smectic C* and antiferroelectric smectic CA * phases were studied by complementary methods in the temperature range from −125 to 120 °C. Differential scanning calorimetry measurements together with polarizing optical microscopy provided the phase sequence, including the glass transition and a cold crystallization. X-ray diffraction was used to obtain the unit-cell parameters of the crystal phase, as well as the layer thickness and correlation length in the liquid crystalline smectic phases. The tilt angle was found to reach 45°, as determined from the measurements of the layer thickness and molecular modeling. Relaxation processes in the smectic phases and the fragility parameter were studied using frequency-domain dielectric spectroscopy.